Swedish Malaise Trap Project (SMTP) - small Sciaroidea families - Dave Karlsson; Fredrik Ronquist (Station Linné, 2020)
Occurrences in this dataset on Swedish Insects have been identified from specimens collected from for the Swedish Malaise Project (SMTP), an inventory funded by the Swedish Species Information Centre (ArtDatabanken). These records comprise the foundation for recent estimates on the size and composition of the Swedish insect fauna, published herein as sample-based datasets.
Keywords: Samplingevent; Sweden; Insecta; Malaise Trap; Sciaroidea; SAMPLING_EVENT; Biological Sciences; Biologi